Building Entrepreneurial Spirit in Students Through Islamic Economic Literacy - Heidy Akhadi; Ahmad Maulidizen; Abdul Haris Muchtar (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This community service program titled